Inventario de aves de Alluriquín, provincia de Santo Domingo de los Tsáchilas - Venegas Sambachi, Roberto Andres (2021)
The objective of this research project was to carry out an inventory of birds in the parish of Alluriquin, province of Santo Domingo de los Tsachilas, obtaining a bird guide as a result of the project that has the purpose of making known the species of birds, their conservation status and where to find them. To do this, a diagnosis of the study area was made, in which the productive conditions of the locality were known, where agriculture and livestock are the main elements for the economy of the same; In addition, the general characteristics of the area were determined, resulting in three study zones: the first zone is located in the center of the Alluriquin parish; the second zone is considered a transition zone with a decrease in the number of inhabitants; it has remnants of partially intervened forest and the presence of cattle ranching; and the third zone has a decrease in the number of inhabitants, The third zone has a remnant of better preserved native forest with little human intervention. Monitoring recorded a total of 755 individuals, distributed in 16 orders, 28 families, 67 species of birds in three different schedules, in zone one 244 individuals belonging to five species were observed: In zone two, 133 individuals were observed in a total of 21 species and in zone three with 237 individuals and a total of 41 species; the zones were compared using the Sorense similarity index, which determined the greatest similarity between zones two and three with 52.50%, then zones one and two with 17.78%, with zones one and three having the least similarity, which contrasts the information used for zoning. According to the International Union for the Conservation of Nature, most of the species are of minor concern; however, there are three species that are in the near-threatened category and one vulnerable species, two of which are only found in zones two and three; two of them are found in zone two and all of them in zone three. Finally, with the data obtained, a descriptive photographic guide was made that summarizes the species found and the areas where they can be observed, making it a tool for bird watching. From this study it can be concluded that the existing zones are different and are home to several species that mainly in zones two and three can demonstrate that there is potential for the development of birdwatching; however, this requires further research to determine the potential and make a plan for the proposal of birdwatching in the study area.